Efficacy and predictors of success on laryngomalacia surgery: experience from a tertiary pediatric care center in Brazil - Renata Loss Drummond; Rita Carolina Pozzer Krumenauer Padoin; Bárbara Duarte Salgueiro; José Faibes Lubianca Neto (Brazilian Journal of Otorhinolaryngology, 2023)
Objectives: Laryngomalacia is the most common congenital cause of stridor; the natural history of the disease runs through to complete resolution by the age of two. Severe cases are characterized by cyanosis, hypoxia, apnea, furcular and/or subcostal retractions, aspirations, pulmonary hypertension, and failure to thrive and must undergo surgery. This study aimed to evaluate the success rates of supraglottoplasty in our hospital and evaluate the predictive factors for surgical success. Methods: Cohort study, prospectively planned. 75 patients undergoing endoscopic surgery from July 2007 to July 2016 were analyzed at the Santo Antônio Children’s Hospital. The primary outcome was percentage of surgical success, defined as the absence of respiratory symptoms or presence of a mild stridor without retractions on the first post-operative month (late success). The secondary outcomes were the early surgical success (absence of respiratory symptoms or presence of a mild stridor without retractions on the first post-operative day). Results: 39 (58.2%) were male, with an average of 4.9 months. Surgical success on the first day was 80.6% (n = 54). At the end of the 1st month, surgical success was 88.6%, considering only those who completed assessment. Twenty-one (34%) presented comorbidities. Presence of comorbidities, pharyngomalacia and GERD were associated with a worse result on the 1st postoperative day, whereas, at the end of the first month, presence of comorbidities, concomitant injuries (tracheo and bronchomalacia) and pharyngomalacia were the predictive variables of surgery failure. Conclusion: Supraglottoplasty has high rates of efficacy and low morbidity. The presence of comorbidities and pharyngomalacia has shown association with a worse early and late surgical outcome. Synchronous airway lesions predict a worse surgical result at the end of the first month. GERD was associated with obstructive symptomatology only in the 1st post-operative day. Level of evidence: Level 3 of evidence, according to the “The Oxford 2011 Levels of Evidence” from Oxford Centre for Evidence-Based Medicine.